2022
DOI: 10.1136/jitc-2022-005328
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and functional analyses of neoantigen-specific CD4 T cells during a profound response to anti-PD-L1 in metastatic Merkel cell carcinoma

Abstract: BackgroundMerkel cell carcinoma (MCC) often responds to PD-1 pathway blockade, regardless of tumor-viral status (~80% of cases driven by the Merkel cell polyomavirus (MCPyV)). Prior studies have characterized tumor-specific T cell responses to MCPyV, which have typically been CD8, but little is known about the T cell response to UV-induced neoantigens.MethodsA patient in her mid-50s with virus-negative (VN) MCC developed large liver metastases after a brief initial response to chemotherapy. She received anti-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
(61 reference statements)
1
6
0
Order By: Relevance
“…However, significant numbers of antigen-specific CD8 T cells were not observed after vaccination with ITI-3000 ( Figure 2D ). This agrees with previous studies using human PBMC and MCC tumor-infiltrating cells that demonstrate strong CD4 T cell-mediated immune responses to the LT antigen ( 16 , 24 , 42 , 43 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, significant numbers of antigen-specific CD8 T cells were not observed after vaccination with ITI-3000 ( Figure 2D ). This agrees with previous studies using human PBMC and MCC tumor-infiltrating cells that demonstrate strong CD4 T cell-mediated immune responses to the LT antigen ( 16 , 24 , 42 , 43 ).…”
Section: Discussionsupporting
confidence: 92%
“…Multiplex immunohistochemistry was performed with a panel of antibodies including CD8 (clone 144B/Dako/fluor 520 opal/concentration 0.2 μg/mL), CD3 (Sp7/Thermo/fluor opal 650), HLA-DR (EP96/BSB/0.125 μg/mL/fluor opal 690), CD56 (123.C3/BSB 1 μg/mL/fluor 540), and PD-L1 (E1L3N 0.5 μg/mL) using a modified Akoya Opal Multiplex IHC assay. 71 We also attempted PD-1 staining with antibody clone D4W2J. However, non-specific staining was observed, and PD-1 was thus excluded from analysis.…”
Section: Methodsmentioning
confidence: 99%
“… 4 , 5 For cancer vaccines, a Th1-skewed response generating neoantigen-specific CD8 cytotoxic T cells is considered desirable. 6 …”
Section: Main Textmentioning
confidence: 99%
“… 1 Most approved adjuvants, used in pathogen vaccines, induce a Th2 response deemed ill-suited for cancer vaccines. 4 , 6 Ligands for pattern-recognition receptors such as Toll-like receptors (TLRs) on APCs have been shown to induce Th1-polarized immune responses, though this appears to additionally depend on their spatial presentation context. 2 , 7 For example, studies on poly(lactic-co-glycolic acid) nanoparticles showed that a higher density of CpGs, a ligand for TLR9, on the nanoparticle induced Th1-polarization, while a lower density favored Th2.…”
Section: Main Textmentioning
confidence: 99%